A Tale of Two Maladies? Pathogenesis of Depression with and without the Huntington’s Disease Gene Mutation - Du, Xin; Pang, Terence Y.; Hannan, Anthony J. (Frontiers in Neurology, 2013)
Huntington’s disease (HD) is an autosomal dominant disorder caused by a tandem repeat expansion encoding an expanded tract of glutamines in the huntingtin protein. HD is progressive and manifests as psychiatric symptoms (including depression), cognitive deficits (culminating in dementia) and motor abnormalities (including chorea). Having reached the 20th anniversary of the discovery of the ‘genetic stutter’ which causes HD, we still lack sophisticated insight into why so many HD patients exhibit affective disorders such as depression at very early stages, prior to overt appearance of motor deficits. In this review, we will focus on depression as the major psychiatric manifestation of HD, discuss potential mechanisms of pathogenesis identified from animal models, and compare depression in HD patients with that of the wider gene-negative population. The discovery of depressive-like behaviours as well as cellular and molecular correlates of depression in transgenic HD mice has added strong support to the hypothesis that the HD mutation adds significantly to the genetic load for depression. A key question is whether HD-associated depression differs from that in the general population. Whilst preclinical studies, clinical data and treatment responses suggest striking similarities, there are also some apparent differences. We discuss various molecular and cellular mechanisms which may contribute to depression in HD, and whether they may generalise to other depressive disorders. The autosomal dominant nature of HD and the existence of models with excellent construct validity provide a unique opportunity to understand the pathogenesis of depression and associated gene-environment interactions. Thus, understanding the pathogenesis of depression in HD may not only facilitate tailored therapeutic approaches for HD sufferers, but may also translate to the clinical depression which devastates the lives of so many people.